(untitled) (Experimental biology, 2015)
Investigations of the mycorrhizal and nonmycorrhizal plants Phaseolus vulgaris L. and Zea mays L. showed that root systems of plants with mycorrhiza were developed more better than nonmycorrhizal ones. Received data show that arbusclular mycorrhiza raises the growth characteristics of host plant considerably increasing the number and the length of as main as additional roots. Owing to the increasing of the root system capacity the volume of used soil is increased too. This increases the abundance of nutritive material available to host plant. Hence, the persistence of plants and its resistance to difficult environments.